The Effect of Economic Growth and Inflation on the Composite Stock Price Index for the Period 2020-2023 - Wahyu Indah Mursalini; Nurhayati Nurhayati; Raihan Najid (International Journal of Social Science and Community Service, 2026)
This investigation aspires to procure empirical substantiation concerning the repercussion of economic expansion and inflation upon the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange (IDX) throughout the span of 2020–2023. The methodological framework employed is regression analysis within a quantitative paradigm, grounded in archival data of IHSG reports. The research cohort was delineated through a total sampling technique, yielding 48 monthly observations consonant with the stipulated criteria.The findings disclose that economic expansion exerts a constructive and statistically momentous influence on the IHSG, evidenced by a t-statistic of 12.638 surpassing the critical threshold of 2.01410, with a probability value of 0.000 < 0.05. Accordingly, hypothesis (H1) is corroborated while the null proposition is repudiated. In contraposition, inflation likewise manifests a significant effect on the IHSG, with a t-statistic of 12,905.184 > 2.01410 and a probability value of 0.003 < 0.05, thereby validating hypothesis (H2).Conjointly, economic expansion and inflation were discerned to wield a simultaneous and notable effect on the IHSG, with an F-statistic of 121.218 exceeding the tabular benchmark of 3.204 and a significance level of 0.000 < 0.05, affirming hypothesis (H3). Thus, the inquiry elucidates that economic expansion assumes a pivotal role in augmenting the IHSG, while inflation also imparts a consequential individual impact. Nevertheless, under a joint analytical lens, both determinants conjointly demonstrate a substantive influence upon the trajectory of the IHSG.